Indigenous agricultural knowledge: A neglected human based resource for sustainable crop protection and production - Melash, Anteneh Agezew; Bogale, Amare Assefa; Migbaru, Abeje Tafere; Chakilu, Gashaw Gismu; Percze, Attila; Ábrahám, Éva Babett; Mengistu, Dejene Kassahun (Elsevier, 2023)
Indigenous knowledge, developed over generations and owned by communities or individuals within a community, offers alternative strategies and perspectives on resource management and use. However, as emphasized in the contemporary agricultural history of Ethiopia, the most effective indigenous agricultural knowledge has not been well documented and some of them are replaced by modern techniques. This study was therefore conducted to assess and document community-based techniques to control pests and diseases and the practical implications of indigenous farming techniques. A focus group discussion, key informant interviews and semistructured questionnaires were conducted with 150 farmers. The result showed that a substan tial number (92%) of the farming community uses indigenous based plant protection measures. Indigenous farmers (92%) splash liquids made of cow urine to control the adverse effect of fungi. Farmers are also using different seed selection methods for next season planting. About 29% of the farmers do single head-based seed selection prior to mass harvesting, 34% are collected as “Qerm” and 45% select their seeds during threshing. Indigenous farming knowledge varies with the natural feature of the growing location and cropping system, including the rainfall pattern, soil fertility status, crop, and weed type. The observed positive effect of indigenous agricultural practices on crop production substantiates the need to include these essential approaches in the cultivation system along with the modern agronomic techniques. This might reduce the dependency on expensive and pollutant agricultural inputs. However, sociodemographic factors such as educational level, marital status and farming experience have been found as a determinant factor that influences utilization of indigenous farming knowledge. It can be therefore inferred that documenting indigenous knowledge and proving its applicability scientifically could contribute to organically oriented agricultural production and consequently reduce agriculture’s contribution to environmental pollution.